HIV preventive vaccines - McMichael, Andrew (Henry Stewart Talks, 2007)
HIV distribution, HIV in Africa, HIV particle, T-cell responses, CD4 T-cells susceptible to HIV infection, CD8 T-cells control HIV infection, Acute HIV infection, HIV escape mutations when CTL response focused on dominant epitope, Immune control of HIV, Antibody response to HIV-1, Viral membrane fusion, 5 broadly neutralizing antibodies, Antibody vaccines for HIV, T-cell vaccine control of HIV, CD8+ T-cell inducing vaccines partly protect against SIV/SHIV challenge, HIVA DNA/MVA immunization in mice and macaques, HIVA DNA + MVA in humans, MVA.HIVA boosts HIV-1-specific CD8 T-cells in HIV+ donors on ART, Current T-cell vaccines for HIV, Phase IIB trials, Merck rAd5 vaccine, The problem of HIV variability, Ways to tackle HIV-1 diversity
Archived at 2018/05/31